Perceptual and Physiological Responses to Jackson Pollock's Fractals - Taylor, Richard; Spehar, Branka; Hagerhall, Caroline; Van Donkelaar, Paul (Frontiers in Human Neuroscience, 2011)
Fractals have been very successful in quantifying the visual complexity exhibited by many natural patterns, and have captured the imagination of scientists and artists alike. Our research has shown that the poured patterns of the American abstract painter Jackson Pollock are also fractal. This discovery raises an intriguing possibility – are the visual characteristics of fractals responsible for the long-term appeal of Pollock’s work? To address this question, we have conducted ten years of scientific investigation of human response to fractals and here we present, for the first time, a review of this research that examines the inter-relationship between the various results. The investigations include eye-tracking, visual preference, skin conductance, and EEG measurement techniques. We discuss the artistic implications of the positive perceptual and physiological responses to fractal patterns.